Transient behaviour and rate effects in resistive detectors - Fraga, M. M. (1998)
The dependence of the detection efficiency (or charge gain) of a resistive detector on the counting rate has been considered by several authors. The influence of the resistivity of the electrodes, the counter geometry and the gas mixture composition have also been studied. Most of those measurements assume a stationary regime. In the present work we report on studies of the transient behaviour of detectors with a resistive cathode for various counting rates, charge gains and detector geometries. We show that in some cases the time-decay curves can be fitted by a single exponential plus a constant term, while in others (higher charge gains or higher counting rates) a sum of two or even three exponentials plus the constant term is needed to fit the experimental data. A study of the electric properties of the dielectrics used is also presented and a comparison is made between these results and the data obtained under irradiation conditions.